Hispanic Studies in Honor of Nicholson B. Adams - Selig, Karl Ludwig; Keller, John Esten (Studies in the Romance languages and literatures ;, 2019)
This volume is composed of fifteen essays on Hispanic subjects by scholars from the United States and abroad, and it was presented to Professor Adams in his seventieth year.